Circulating miRNAs in patients with Barrett’s esophagus, high-grade dysplasia and esophageal adenocarcinoma - Pavlov, Kirill (J Gastrointest Oncol, 2018)
BACKGROUND: Diagnostic screening of premalignant esophageal lesions is hampered by the absence of biomarkers indicative of metaplastic and/or malignant transformation. The aim of this exploratory study was to investigate the potential use of miRNAs as biomarkers capable of identifying patients with (pre)malignant lesions: Barrett’s esophagus (BE) metaplasia, high-grade dysplasia (HGD) or esophageal adenocarcinoma (EAC). METHODS: A total of 69 patients were included in the study. Six serum samples from each of four study groups, i.e., patients with normal squamous epithelium (SE), BE, HGD and EAC, were profiled using the Nanostring miRNA analysis platform. Differential miRNA expression patterns then were validated in 69 patient samples using qRT-PCR. RESULTS: miRNA expression profiling revealed seven miRNAs with a 2-fold change in expression level. Validation by qRT-PCR confirmed that serum miR-320e levels were significantly decreased in the BE group compared to the SE (P≤0.001, AUC 0.790) and HGD groups (P≤0.005, AUC 0.786). Serum miR-199a-3p levels were significantly decreased in the BE group compared to the SE group (P≤0.001), area under the curve (AUC) of 0.813. CONCLUSIONS: The results of this study suggest that decreased serum miRNA levels of miR-199a-3p and miR-320e could help to identify patients with BE and HGD.